The Comprehension of Halal Certification for Leathercraft Industry in The Local Business - Pane, Syaiba Lingga; Kusuma, Suteja Wira Dana (Likuid Jurnal Ekonomi Industri Halal, 2023)
The Halal Product Guarantee Act states that all products circulated and traded in Indonesia must be halal certified, including non-food use items such as leather handicraft products. Moreover, this product is made from animal skin which has many critical points so a halal certificate is needed to guarantee the halalness of the product. Halal certificates are obtained through a certification process that must be fulfilled by producers or entrepeneur. The purpose of this study is to determine the level of understanding of producers or business actors of the leather craft industry about halal certification and to know the obstacles faced by business actors of the leather craft industry about halal certification. This research is qualitative research with a descriptive analysis method. Data collection was obtained through interview techniques with leather craft industry entrepreneurs in Sukaregang Garut. Based on the results of the study, the researcher concluded that entrepreneurs with low understanding were 20%, entrepreneurs with moderate understanding were 40%, and entrepreneurs with perfect understanding were 40%.